2023
DOI: 10.3390/nu15153413
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a Multitasking Molecule That Improves Skeletal Muscle Health

Luana Toniolo,
Monica Concato,
Emiliana Giacomello

Abstract: Resveratrol is a natural polyphenol utilized in Chinese traditional medicine and thought to be one of the determinants of the “French Paradox”. More recently, some groups evidenced its properties as a calorie-restriction mimetic, suggesting that its action passes through the modulation of skeletal muscle metabolism. Accordingly, the number of studies reporting the beneficial effects of resveratrol on skeletal muscle form and function, in both experimental models and humans, is steadily increasing. Although stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Although recent studies are pointing towards the importance of sex-dependent differences in skeletal muscle form and function [58][59][60][61], very often, research protocols and clinical trials entail mainly males [62]. In this context, in a recent review on human trials to test the effect of Resveratrol on skeletal muscle function, we reported that only 9 out of 24 clinical trials involved women [63]. Based on the distinct sex-dependent development of diet-induced metabolic dysregulation described here and in other works, the potential of skeletal muscle-directed strategies should be reconsidered.…”
Section: Discussionmentioning
confidence: 84%
“…Although recent studies are pointing towards the importance of sex-dependent differences in skeletal muscle form and function [58][59][60][61], very often, research protocols and clinical trials entail mainly males [62]. In this context, in a recent review on human trials to test the effect of Resveratrol on skeletal muscle function, we reported that only 9 out of 24 clinical trials involved women [63]. Based on the distinct sex-dependent development of diet-induced metabolic dysregulation described here and in other works, the potential of skeletal muscle-directed strategies should be reconsidered.…”
Section: Discussionmentioning
confidence: 84%
“…Clinical research with drugs and biologics intended to slow or reverse normal aging processes has only recently begun [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Positive results are beginning to emerge from the very numerous clinical trials (and observational studies) launched worldwide (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Human sirtuins are a family of 7 signaling NAD + -dependent protein deacetylases that are involved in metabolic regulation, resistance to stress, and cellular processes, including aging and cell death [10,11]. The natural polyphenol resveratrol is a powerful activator of sirtuin-1 (SIRT1) [12,13].…”
Section: Sirtuin Activatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding nutrition, numerous plant-derived natural compounds have demonstrated their capacity to induce muscle growth and hypertrophy, including curcumin, resveratrol, green tea, and ginkgo biloba extract [ 6 , 7 , 8 ]. Among them, over the past 20 years, there has been a growing interest in and demand for Lepidium meyenii Walp, or maca, due to its health benefits [ 9 ].…”
Section: Introductionmentioning
confidence: 99%